2008
DOI: 10.1103/physrevd.77.063524
|View full text |Cite
|
Sign up to set email alerts
|

CosmicLi6andLi7problems and BBN with long-lived charged massive particles

Abstract: Charged massive particles (CHAMPs), when present during the Big Bang nucleosynthesis (BBN) era, may significantly alter the synthesis of light elements when compared to a standard BBN scenario. This is due to the formation of bound states with nuclei. This paper presents a detailed numerical and analytical analysis of such CHAMP BBN. All reactions important for predicting lightelement yields are calculated within the Born approximation. Three priorly neglected effects are treated in detail:(a) photodestruction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
126
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 52 publications
1
126
0
Order By: Relevance
“…They then found that 9 Be * (1/2 + , 1.684 MeV) X is not a resonance but a bound state located below the 8 Be X +n threshold. The resonant 8 Be X (n,X − ) 9 Be X reaction is thus not likely to contribute.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…They then found that 9 Be * (1/2 + , 1.684 MeV) X is not a resonance but a bound state located below the 8 Be X +n threshold. The resonant 8 Be X (n,X − ) 9 Be X reaction is thus not likely to contribute.…”
mentioning
confidence: 99%
“…[7]). A resonant reaction 8 Be X (n,X − ) 9 Be through the atomic ground state of 9 Be * (1/2 + ,1.684 MeV) X , i.e., an atom composed of the 1/2+ nuclear excited state of 9 Be and an X − particle, has also been suggested as a possible reaction to produce mass 9 nuclides [10]. Kamimura et al [9], however, adopted a root mean square charge radius for 8 Be of 3.39 fm as a more realistic input.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Their derived abundances in metal-poor stars are difficult to reconcile simultaneously with standard predictions. Different production sites in the early Galaxy have been discussed: Big Bang nucleosynthesis (Wagoner et al 1967;Nollett et al 1997;Coc et al 2004;Jedamzik 2008), cosmic ray spallation and/or α-fusion (Reeves et al 1970;Vangioni-Flam et al 2000) and neutrino spallation (see e.g. Vangioni-Flam et al 1996).…”
Section: Introductionmentioning
confidence: 99%